Analysis of factors affecting the accountability of village fund management at village government - Diansari, Rani Eka; Othman, Jaizah; Musah, Adiza Alhassan; Adhivinna, Vidya Vitta; Sutari, Tri (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2022)
In order to determine whether or not certain factors have an effect on the accountability of village money, this study looks at a variety of factors, including the use of information technology, community participation, internal control mechanisms, and prosocial behavior. The sample for this research comes from the entire community of Kapanewon Imogiri, which is located in the Bantul Regency. In total, there were 48 persons who agreed to take part in this study. The research method that was used was a non-probability sampling method that utilized a saturated sampling type. The information was gathered through the use of a questionnaire. The study of the data consisted of using multiple forms of linear regression. The findings demonstrated that the utilization of information technology has an impact on the accountability of the management of village funds. Accountability in the management of village funds is unaffected by community participation, institutional control systems, or prosocial behavior